Clinicopathological correlation of abdominal hysterectomy - Manandhar, Tara; Sitaula, Sarita; Dixit, Baburam Thapa; Agrawal, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysterectomy is the most common gynaecological procedure performed worldwide. Abdominal hysterectomy remains the most common approach though recently there has been preference towards laparoscopic hysterectomy. Fibroid uterus is the most common indication for hysterectomy followed by pelvic organ prolapse, benign ovarian tumour and abnormal uterine bleeding. The objective of this study was to analyse the indication, outcome and correlate the clinical indication with the histopathological diagnosis. Methods: This study was conducted in the Department of Obstetrics and Gynaecology, B. P. Koirala Institute of Health Sciences, from January 2017 to December 2019. This is a descriptive analysis of the patients who had undergone abdominal hysterectomy during the study period. Results: A total of 801 patients underwent abdominal hysterectomy and the most common indication was fibroid uterus (n=391, 48.81%), followed by abnormal uterine bleeding. The total complication rate was 3.24% (n=26) and we had one (0.1%) mortality. Histopathological analysis of the specimen revealed leiomyoma (54.43%) as the most common finding. The clinical indication and histopathological diagnosis matched in 373 (86.94%) patients. Conclusions: Abdominal hysterectomy is the most common approach and it is associated with risk of complications, so the indication for hysterectomy should be adequately evaluated. With the improvement in the different organ-preserving options, hysterectomy in benign disease should only be opted when all the other conservative options fails.